DAMPAK IMPLEMENTASI MANDAT KONSUMSI BAHAN BAKAR NABATI TERHADAP PEREKONOMIAN INDONESIA - Sugiyono Sugiyono; Rina Oktaviani; Dedi Budiman Hakim; Bustanul Arifin (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2012)
Before 2006, biofuel mandate consumption was expected to contribute to increase economic growth and job creation, decrease poverty, mitigate climate change, and improve energy security. The objective of the study is an analysis of implementation of biofuel mandate in Indonesian economy. This research applied the long run of Recursive Dynamic General Equilibrium (RDGE) model by Indonesian Forecasting. Three simulations are used to increase of biofuel demand, seconds to increase of biofuel agriculture land expansion, deforestation, and rise fixed capital, and to last change agricultural and biofuel productivity. The policy of biofuel mandate implementation is effectively to increase economic growth, rise household income, and improve carbon emission, but less effective to built food security and feed, decline employment by industri for non biofuel agriculture, and descend forest and other forest outputs in Indonesia. The policy implication is to increase output for non biofuel agriculture by rising productivity and policy of import and inflation targetting to take sides for welfare farmer’s and food employee’s.  Keywords: Biofuel, RDGE, food security, carbon emission